The Design of DC 12 V to DC 380 V 1000 Watt Converter with ATmega328 as a 65 KHz Oscillator - Brahmana, Kurnia (Talenta Publisher, 2020)
A DC to DC converter has been built and research has been conducted to examine the effect of load on the output voltage of the DC to DC converter with fixed oscillation frequency. This converter DC to DC circuit uses a 12 V DC battery as an input voltage source connected with a step-up transformer until it is successfully raised to 380 V DC. The load given to the DC to DC circuit converter in the form of lamps, varies from 40 watts to 960 watts with a fixed oscillation frequency of 65 Khz that has been determined by the microcontroller. The test results showed that the output voltage value decreased in accordance with the increase in load so that when the load of 960 watts obtained the output voltage of 220 V DC.